GAMBARAN MOTIVASI DAN PARTISIPASI KELUARGA DALAM PERAWATAN MANDIRI PASIEN GAGAL JANTUNG - Adella Indri Afitasari; Beti Kristinawat (Jurnal Ilmu Keperawatan Medikal Bedah, 2020)
The inability of the heart to pump blood adequately accompanied by dyspnea causes people with heart failure to have physical limitations. These symptoms result in the patient being unable to perform self-care optimally, so they need help from others, especially family. This study aims to identify the description of motivation and family participation in the self-care of heart failure patients. The research design used was descriptive quantitative research with 152 respondents who were drawn by purposive sampling technique. The results showed 62.5% women, and aged between 40-59 years. Forms of family motivation are family care about the patient's illness, family acceptance of the patient's condition, and family assistance to a health service center. Family participation was divided into three, with the highest score being self-care management who contacted the doctor or nurse, and advised the family to take medication when symptoms appeared. Participate in self-care with an assessment of readiness to work, and follow given medication instructions. Then the maintenance of self-care, namely leaving the family to exercise control with a doctor or nurse, and treatment of patients so they don't drink, forget to drink using a medicine box.